HOW PRIVATE EQUITY ENHANCES LONG-TERM PORTFOLIO GROWTH IN WEALTH MANAGEMENT. - Gaikwad, Anay Vilas; Kulkarni , Sameer .A.; Sharma Padroo, Bhawna (International Journal of Research -GRANTHAALAYAH, 2025)
Private equity (PE) has evolved into a critical component of modern wealth-management strategies due to its potential to generate superior long-term returns and enhance portfolio diversification. This study examines how integrating private equity into wealth-management portfolios contributes to sustained value creation for high-net-worth investors. Through an analysis of academic literature, industry trends, and practical insights from internship experience, the research highlights the mechanisms through which private equity creates value ranging from active management and operational improvements to strategic exits and innovation-driven growth. The findings indicate that portfolios with private equity exposure benefit from higher risk-adjusted performance, improved diversification, and greater resilience to market volatility. This study concludes that private equity is not only a return-enhancing asset class but also a strategic tool that supports long-term wealth accumulation and financial stability.